A recepção na obra de Cláudia Tajes - Oliveira, Joicylene Sabóia de (2015)
A recepção na obra de Claudia Tajes intends to analyze aspects of a literature that is concerned about the reader, takes risks in the plot of Taje´s characters and aims at modern ways of communication. In order to raise readers and readings, Tajes uses paratexts such as expressive titles and elaborate covers with verbal and iconographic indications, contributing in part to the interest of the media so that the texts were adapted to theater, cinema and television. Based on this interest in adaptations we have chosen five of her characters in order to understand their aesthetic experiences. For the presence of humor is part of the language in Taje´s books, we used postulates of Skinner (2004), Bergson (1983) and Bakhtin (2013) for verifying the reception of humor, trying to know whether the laughter is created by the ridicule or catharsis. We also observed Taje´s interlocutors such as the critical in which is latent the inclusion of the author in the mass literature which refers to the principles of Eco (2011) and Aranha (2009). Therefore our proposal concerns about the elements of reception, author, text and reader whose materializations circulate in the creative universe. Keywords: Claudia Tajes, literary representation, reading, paratexts.